Impact of work environment on cardiovascular diseases in Denmark. Issue 1 (March 1991) - Olsen, O; Kristensen, T S
Abstract : STUDY OBJECTIVE–The aim was to estimate the quantitative impact of working conditions on cardiovascular diseases in Denmark. DESIGN–The study was based on a review of recent epidemiological research publications in which relative risks were estimated and risk factor prevalences were determined. The impact of working conditions was quantified by means of aetiological fractions. SETTING–The aetiological fractions were estimated on the Danish population. MAIN RESULTS–16% of the premature cardiovascular mortality in men and 22% in occupationally active women is avoidable through interventions in the work environment. If "sedentary" work is included in the occupational risk factors, the aetiological fractions reach 51% for men and 55% for women. Taken separately, the major aetiological fractions for cardiovascular risk factors at work are respectively (women in parentheses) 6% (14%) for monotonous high paced work, 7% (7%) for shift work, and 2% (2%) for passive smoking. CONCLUSIONS–The aetiological fractions show that working conditions play a considerable role in cardiovascular diseases. Furthermore they might widen the focus of preventive cardiology from interventions directed only at individual and lifestyle risk factors to interventions directed also at working conditions.